MODIFICATION OF LAYER CHARGE IN SMECTITES BY MICROWAVES - Zemanová M.; Link G.; Takayama S.; Nüesch R.; Janek M. (My University, 2006)
The layer charge reduction of two Li-saturated montmorillonites is referred to application of microwave radiation at 2.45 GHz for dispersions and 30.0 GHz for the solid powders. Efficiency of these treatments was compared to the same conditions applying conventional heating. The samples were heated in the temperature and time windows corresponding to 190-270 °C and 30-120 min, respectively. Changes in the mean layer charge were monitored by the determination of cation exchange capacity values using exchange of triethylene tetraamino copper ions. The charge reduction of the montmorillonites in aqueous dispersions was rather low (< 30%) despite the fact, that high Li+ concentration dissolved in solution was selected (1 mol L- 1). This behaviour was attributed to the very high water content in used dispersions and high hydration enthalpy of Li+ cations. Nevertheless, the microwave heated dispersions (2.45 GHz) showed detectable layer charge reduction as compared to conventionally heated dispersions, where no significant changes were found. Solid powders with different content of exchangeable lithium ions were prepared with solutions having different molar fraction of Li+ and Na+ cations (0%, 20%, 40%, 60%, 80%, 100% of Li+). Final composition of interlayer cations was analysed with ICP-OES. In contrary to dispersions, the microwave treatment of the prepared powders revealed high layer charge reduction, which was much higher than for conventionally heated powders. The efficiency was enhanced with increasing interlayer lithium content but reached a limiting value depending on the montmorillonite used. Migration of the lithium into the structure of the montmorillonite supported with microwaves was extremely fast, finished probably within the few minutes of the treatments. The exchangeable Li+ cations are accelerated through alternating electric field of microwaves and highly efficient layer charge neutralisation occurs. Infrared spectroscopy showed that the products obtained with microwave treatments correspond to the materials heated conventionally for much longer periods of time. Hence, applying microwaves the time and energy requirement can be significantly reduced. The X-ray diffraction showed that montmorillonite layers were able to swell in ethyleneglycol upon charge reduction, if the cation exchange capacity was not reduced more than 20-40%. © 2006 Elsevier B.V. All rights reserved.
Keywords: CATION EXCHANGE CAPACITY; HOFMANN-KLEMEN EFFECT; LAYER CHARGE; LITHIUM MONTMORILLONITE; MICROWAVES; SMECTITE